PLAGIARISME, UPAYA PENCEGAHAN, PENANGGULANGAN DAN SOLUSINYA - Lilis Sulistyaningsih (Central Library of Universitas Sebelas Maret, 2017)
Plagiarism has been plagued primarily by technological developments that allowthe cheating to be more easily implemented. It is our duty to prevent the epidemic.Awareness to reject plagiarism should not be broken. Allowing the practice ofplagiarism proceeds in the same way as to let the world of education be plagued bya moral epidemic that further alienates society from the values of honesty, virtue andnobility.To prevent the occurrence of plagiarism, among others can be done by: 1)Honesty in a writer; 2) Recognition of the work of others; and 3) Increasing the roleof educators in preventing plagiarism. Seeing the many adverse effects of plagiarism,appropriate handling and mitigation is necessary. There are several solutions thatcan be practiced to overcome plagiarism include: 1) fostering a sense of integrityand shyness plagiarize in academia; 2) Improving the function and role of researchsupervisors; 3) Provide clear and explicit sanctions against plagiarism perpetrators;4) Establish a journal data bank in each research institute; 5) Using anti plagiarismsoftware. There are several examples of software applications that can be used include:Turnitin test, Wcopyfind test, Viper test, and Article Checker test